Determinantes del rendimiento educativo de los estudiantes de secundaria en Cali: un análisis multinivel - Correa, John Jairo (Sociedad y Economía, 2004)
This paper analyses the effect of several variables on the school performance of students of Cali in the eleventh grade (the higher school level). The variables analyzed are the following: personal characteristics of the students, school variables, and their interaction. The data were collected from 427 schools of Cali for a sample of 16,998 students. Multilevel lineal modeling with two levels was used for the analysis. It was found that there are significant differences between the school performance of the students, and these are explained mainly by factors that operate through differences between schools and students